A meta-analysis on the crossover of workplace traumatic stress symptoms between partners. - Wang, Yi-Ren; Ford, Michael T.; Credé, Marcus; Harms, P. D.; Lester, Paul B. (Journal of Applied Psychology, 2023)
= .26), suggesting that workers' PTSD/distress is as distressing for partners as the traumatic stressors are for workers encountering them firsthand. Our moderation tests further revealed that the trauma-exposed workers' vulnerability to traumatic stress symptoms was stronger in military than in nonmilitary settings, whereas the extent to which their symptoms crossover to their intimate partners did not vary across occupations. Mediation tests suggest that traumatic stress crossover is partially explained by the worsened quality of the couple's relationship (e.g., increased social support burden and undermining), consistent with the crossover via couple interaction explanation in crossover theory. On the other hand, there was mixed support for the mediating role of the partner's empathy, indicating further research and clarification are needed. Implications for crossover theory and practice are discussed. (PsycInfo Database Record (c) 2023 APA, all rights reserved).